Virtual ancestor reconstruction: Revealing the ancestor of modern humans and Neandertals. Issue 91 (February 2016) - Mounier, Aurélien; Mirazón Lahr, Marta
Abstract: The timing and geographic origin of the common ancestor of modern humans and Neandertals remain controversial. A poor Pleistocene hominin fossil record and the evolutionary complexities introduced by dispersals and regionalisation of lineages have fuelled taxonomic uncertainty, while new ancient genomic data have raised completely new questions. Here, we use maximum likelihood and 3D geometric morphometric methods to predict possible morphologies of the last common ancestor of modern humans and Neandertals from a simplified, fully resolved phylogeny. We describe the fully rendered 3D shapes of the predicted ancestors of humans and Neandertals, and assess their similarity to individual fossils or populations of fossils of Pleistocene age. Our results support models of an Afro-European ancestral population in the Middle Pleistocene ( Homo heidelbergensis sensu lato) and further predict an African origin for this ancestral population.